Moving to higher ground: building innovation capabilities to overcome conceptual biases in new product development - Thuillier, Antoine; Fuller, Matthew; David, Albert (HAL CCSD, 2017)
Startup companies face many challenges in the early years of their existence. During these critical stages, they are often required to convince decision makers to allocate critical resources to themto obtain venture capital, support from a startup incubator, orgovernment subsidies